Lumbar Spine Injury/Pathology as a Predictor of Outcomes in National Football League Athletes. Issue 7 (29th July 2014) - Lynch, Thomas Sean; Schroeder, Greg; Gibbs, Daniel; Chow, Ian; LaBelle, Mark; Savage, Jason W.; Patel, Alpesh; Hsu, Wellington; Nuber, Gordon W.
Objectives: The purpose of this study is to determine if a pre-existing lumbar diagnosis such as spondylosis, a herniated lumbar disc, or spondylolysis affects a football player's draft status or his performance and longevity in the NFL. Methods: The written medical evaluations and imaging reports of prospective professional American football athletes from 2003-2011 from one NFL franchise during the NFL combine (annual college football player evaluation prior to the NFL draft) were compiled and evaluated. All players were evaluated for a pre-existing lumbar diagnosis which were compiled from previous injury/medical records including radiographic imaging reports. Those players with a lumbar spine diagnosis and with appropriate radiograph, MRI and CT imaging were included in this study. These athletes were then matched by age, position, year, and round drafted to control draftees without a lumbar spine diagnosis. Career statistics were compiled including length of play and number of games started. Additionally, a previously established "Performance Score" was calculated for all players excluding offensive linemen. The continuous variables of each cohort were compared using a two-sided (tailed) Student's t-test for normally distributed data. A chi-squared analysis was performed to analyze the categorical data. Statistical significance was accepted with a p < 0.05. Results: Out of a total of 2, 965 athletes evaluated from the NFL combine, 414 players were identified with a pre-existing lumbar spine diagnosis. Athletes who attended the NFL combine without a lumbar spine diagnosis were significantly more likely to be drafted than those with one (74% vs. 61% respectively, p < 0.01). There was no difference between the investigational and control group with regard to round drafted, age, year drafted, or position. Overall, athletes with a lumbar spine injury compared to the control group had no difference in the number of years played (4.0 vs. 4.3 years, respectively, p = 0.13), games played (46.5 vs. 50.7, respectively, p = 0.15), games started (28.1 vs. 30.6, respectively, p = 0.39) or performance score (1.4 vs. 1.8, respectively, p = 0.3) (Figure 1). Conclusion: The data in this study suggests that a pre-existing lumbar spine diagnosis was associated with a significantly lower draft status for NFL athletes. However, the data in our study suggests that such a diagnosis did not affect a player's career longevity or performance. Further study will be required to determine the individual effects of specific conditions on performance.